Effects of bombesin on gastrin and gastric acid secretion in patients with duodenal ulcer. Issue 3 (March 1983) - Fave, G Delle; Kohn, Anna; De Magistris, Laura; Annibale, B; Bruzzone, R; Sparvoli, C; Severi, Carola; Torsoli, A
Abstract : The effect of bombesin, a possible neurotransmitter of gastrin release, upon gastrin and gastric acid secretion was investigated in 25 patients with duodenal ulcer and in 16 normal subjects. In patients with duodenal ulcer bombesin (10 ng/kg/min) produced an increase in plasma gastrin output (median 22·4 (range 7·5-75·8) pmol/l/min) similar to that obtained in normal subjects (median 24·4 (range 5·8-56·5) pmol/l/min), whereas gastrin stimulated by a meal was significantly higher in the group of patients with duodenal ulcer (median 20·7 (range 9·2-42·9) vs 16·2 (range 3·4-22·2) p<0·05). Peak acid output induced by bombesin was significantly higher in patients with duodenal ulcer than in normal subjects (median 24·4 (range 9·0-63·8) vs 14·0 (range 3·0-24·8) mmol/h, p<0·05) despite identical gastrin outputs. The ratio (%) obtained by dividing the acid secretory response to bombesin by the response to pentagastrin, however, was similar in both normal subjects and patients with duodenal ulcer (median 55 (range 20-116) vs 58 (range 31-95) respectively). The difference between the gastrin response to food and bombesin could be explained by the fact that bombesin releases gastrin directly, whereas a protein meal involves several mechanisms (neural, peptidergic, paracrine, endocrine), either stimulatory or inhibitory. The above results indicate that a higher concentration in antral and/or duodenal gastrin is unlikely to be present in patients with duodenal ulcer. An increased parietal cell mass could explain the higher gastric acid response after bombesin infusion in our group of patients with duodenal ulcer.